Ku-Klux : The Birth of the Klan during Reconstruction - Parsons, Elaine Frantz, 1970- (Book collections on Project MUSE., 2015)
"The first comprehensive examination of the nineteenth-century Ku-Klux Klan since the 1970s, Ku-Klux pinpoints the group's rise with startling acuity. Historians have traced the origins of the Klan to Pulaski, Tennessee, in 1866, but the details behind the group's emergence have long remained shadowy. By parsing the earliest descriptions of the Klan, Elaine Frantz Parsons reveals that it was only as reports of the Tennessee Klan's mysterious and menacing activities began circulating in northern newspapers that whites enthusiastically formed their own Klan groups throughout the South. The spread of the Klan was thus intimately connected with the politics and mass media of the North"--